2017
DOI: 10.1038/srep43610
|View full text |Cite
|
Sign up to set email alerts
|

Broad spectrum antiviral activity for paramyxoviruses is modulated by biophysical properties of fusion inhibitory peptides

Abstract: Human paramyxoviruses include global causes of lower respiratory disease like the parainfluenza viruses, as well as agents of lethal encephalitis like Nipah virus. Infection is initiated by viral glycoprotein-mediated fusion between viral and host cell membranes. Paramyxovirus viral fusion proteins (F) insert into the target cell membrane, and form a transient intermediate that pulls the viral and cell membranes together as two heptad-repeat regions refold to form a six-helix bundle structure that can be speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 42 publications
7
72
0
Order By: Relevance
“…Sera from African green monkeys (AGMs) were tested in an interferon type I (IFN-I) bioassay based on the protection from vesicular stomatitis virus infection, as described previously [25] Golden Hamster Infection Eight-week-old female Syrian golden hamsters (Mesocricetus auratus; Janvier, Le Genest-Saint-Isle, France) were infected intranasally (i.n.) with 10 4 to 10 6 plaque-forming units (pfu) of NiV in 40 µL or 100 µL DMEM [11]. Groups of 6-12 animals were treated daily with peptide i.n.…”
Section: Interferon Type I Bioassaymentioning
confidence: 99%
See 2 more Smart Citations
“…Sera from African green monkeys (AGMs) were tested in an interferon type I (IFN-I) bioassay based on the protection from vesicular stomatitis virus infection, as described previously [25] Golden Hamster Infection Eight-week-old female Syrian golden hamsters (Mesocricetus auratus; Janvier, Le Genest-Saint-Isle, France) were infected intranasally (i.n.) with 10 4 to 10 6 plaque-forming units (pfu) of NiV in 40 µL or 100 µL DMEM [11]. Groups of 6-12 animals were treated daily with peptide i.n.…”
Section: Interferon Type I Bioassaymentioning
confidence: 99%
“…Weight and temperature were measured after each anesthesia. Blood sampling was on days −1, 2, 4, 6,8,11,13,15,18,20,22,25, and 28 p.i. Hematology was analyzed using MS9-5 (Melet Schloesing) within 4 hours after collection in EDTA-containing tubes.…”
Section: African Green Monkey Infection and Peptide Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion peptide inserts into the outer leaflet of the plasma membrane of the host cell initiating membrane fusion process [5][6][7][8][9]. Understating fusion mechanism not only garners knowledge of virus pathology but also can be exploited for the development of antiviral drugs [10][11][12][13][14]. Consequently, atomic-resolution structures of fusion proteins have provided important molecular insights for the membrane fusion process [2,4,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the majority of research into the fusion function of RSV F has been focused on regions within the F 1 subunit, in particular, the HRA and HRB coiled coil (23)(24)(25). While these studies have provided deeper insight into formation and antiviral targeting of the terminal 6HB fusion core (26), the roles of residues and domains within the F 2 subunit remain relatively unexplored. Here, we performed a comprehensive mutational analysis of the HRC ␣-helix (Lys-75 to Met-97) and demonstrated that the region has an important role in RSV F-mediated membrane (21).…”
Section: Discussionmentioning
confidence: 99%